Mengembangkan Kecerdasan Kinestetik Anak SD dengan Pelatihan Pembuatan Jumputan Untuk Asesoris Interior - Putri Sekar Hapsari; Siti Badriyah; Tri Prasetyo Utomo (Abdi Seni, 2020)
This community service activity aims to improve children's kinesthetic intelligence and to introduce local cultural arts to children from an early age, by taking partnersin two state primary schools in Serengan district at the age of 7-12 years.The reason for taking samples at this age is because children of that age have entered a concrete operational stage, where children have the ability to group,arrange and connect / count numbers or numbers. The training that will be carried out is to provide provision of batik practice learning with jumputan techniques to increase children's experience, knowledge and creativity, especially in the areaof handicraft skills. Children aged 7-12 years tend to have a high level of activity, so this activity if directed properly will be able to increase the kinestheticintelligence it has. There are limitations to the lack of class hours to learnvarious skills, especially batik because it is incorporated into SBDP subjects. The absence of optimizing the kinesthetic intelligence in the batik making field and the lack of insight and knowledge of teachers about the practice of makingbatik. Based on these findings, training needs to be held, one of them is the practice of batik making to optimize the potential of kinesthetic intelligence. So that children can be trained which later can bring up student creativity.Besides that, children have more insight and understanding of local culturalarts by producing a product that can be efficient. This activity is planned fora period of six months, planned activities in the form of: counseling about batikas a legacy of local cultural arts, training in pattern making / design, practice ofusing practical and appropriate tools, coloring practices, then training in developing batik patterns / designs that in the market right now. Keyword : Develop kinesthetic intelligence, batik jumputan, elementary school